2006
DOI: 10.1007/s10750-006-0340-8
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic picoplankton of Lake Baikal: composition, abundance and structure

Abstract: Investigations of Baikalian phytoplankton in 1960s showed that some very small blue-green algae with a cell diameter of 1.5 lm develop in great abundance in Lake Baikal in summer. They were described as a new endemic species -Synechocystis limnetica Popovsk. S. limnetica was found as mass dominant species of the autotrophic picoplankton. Knowledge on species composition of Baikalian picoplankton is limited to this species. Autotrophic picoplankton (APP) communities were studied monthly from 1997 to 2001 at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
4
18
0
Order By: Relevance
“…On the other hand, in LGL, the P A dynamics was strongly influenced by temperature and irradiance seasonality and, in particular, temperature explained the P A fluctuation along the year for picoplankton. This observation has also been reported in several studies regarding picoplankton abundance (Belykh et al, 2006;Mózes et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, in LGL, the P A dynamics was strongly influenced by temperature and irradiance seasonality and, in particular, temperature explained the P A fluctuation along the year for picoplankton. This observation has also been reported in several studies regarding picoplankton abundance (Belykh et al, 2006;Mózes et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…In natural prey assemblages, calanoid copepods frequently prefer ciliates over nanoflagellates (Burns & Schallenberg, ; Yoshida et al., ), and consume very few APP because of their small size (Sommer & Sommer, ). Although aggregated cells of APP are ingested by marine copepods (Wilson & Steinberg, ), such aggregates are rare in the top 50 m of Lake Baikal (Belykh et al., ), and they were seldom seen in our samples. Finally, an early experiment exploring feeding rates of E. baikalensis suggested this copepod is bacterivorous (Afanasyeva & Messeneva, ), but the lack of replication compromised the results, and subsequent experimental work concluded that grazing rates of Epischura on bacteria are low (Stom et al., ).…”
Section: Discussionmentioning
confidence: 78%
“…However, large mucous‐bound colonies (60–130 μm greatest axial linear dimension [GALD]), probably the cyanobacterium Microcystis , were not enumerated because they were assumed to be unsuitable for grazing due to their large size and gelatinous matrix (Sommer & Sommer, ). Cells within APP aggregates averaged nine to 14 cells, but they were not included in total APP counts because they occurred in <15% of the fields of view, and they contribute a negligible proportion (1%–2%) to total APP abundance throughout most of the year in Lake Baikal (Belykh et al., ). Because a trophic cascade might alter the size of APP cells (Zöllner, Santer, Boersma, Hoppe, & Jürgens, ), we also measured the diameter (μm) of 10 APP cells on one to three microscope slides from each of the Control and EPI treatments per experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The filters for bacteria counting were stained with 4 0 ,6-diamidino-2-phenylindole (DAPI) solution. Picoplanktonic cyanobacteria were detected using the phycobilin autofluorescence as described previously (Belykh & Sorokovikova, 2003).…”
Section: Sampling and Counting Of Bacteriamentioning
confidence: 99%